1991
DOI: 10.1007/bf01703140
|View full text |Cite
|
Sign up to set email alerts
|

Cyclosporine-induced graft-versus-host disease after autologous bone marrow transplantation in hematological malignancies

Abstract: In the attempt to induce graft-vs-host disease (GVHD) in patients undergoing autologous bone marrow transplantation (ABMT) or blood stem cell transplantation (BSCT), 12 consecutive patients received cyclosporin A (CyA) post transplant. CyA was given at a dose of 1.5 mg/kg/day intravenously for 28 days, starting on the day of transplant. Histologically proven acute GVHD of the skin occurred in seven patients 9-14 days after ABMT and lasted 7-11 days. CyA-induced GVHD after ABMT resembles mild GVHD after allogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
11
0

Year Published

1992
1992
2003
2003

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…13 Our results indicate that GVHD can be safely and reproducibly induced by 1.5 mg/kg/day CsA intravenously for 28 days following ABMT and APBSCT in childhood. In agreement with previous studies, [13][14][15][16][17][18] CsA-induced GVHD was mild, self-limiting, and confined to the skin. No patients exhibited extracutaneous manifestations of GVHD.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…13 Our results indicate that GVHD can be safely and reproducibly induced by 1.5 mg/kg/day CsA intravenously for 28 days following ABMT and APBSCT in childhood. In agreement with previous studies, [13][14][15][16][17][18] CsA-induced GVHD was mild, self-limiting, and confined to the skin. No patients exhibited extracutaneous manifestations of GVHD.…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, Barredo et al 26 recently reported an unusual case of severe and progressive GVHD following ABMT and CsA therapy. Corresponding to the data in adults, [13][14][15][16][17][18][19] histologically proven CsA-induced GVHD developed after a conditioning regimen that included chemotherapy alone and chemotherapy with total body irradiation and was observed following both ABMT and APBSCT (Table 1). In all cases, acute GVHD of the skin developed during the initial phase of engraftment while the patients were receiving CsA.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…[5][6][7] It is thought eral studies have reported the successful induction of autologous GVHD using cyclosporin A and/or ␣-interferon. 8,9 However, although in vitro studies have shown that the although attempts to reduce the dose of prednisolone below 10 mg daily have been unsuccessful and he continues to effector cells of autologous GVHD can have a graft-versustumour effect, 10 significant in vivo antitumour activity of have some mild chronic changes.…”
mentioning
confidence: 99%